SOCIAL ATTRACTIVENESS OF ALTERNATIVE SOURCES OF INVESTMENT IN MODERN RUSSIA - A. N. Zubets (Финансы: теория и практика)
Today, new tools appear on financial markets to ensure fund raising for various projects aimed at obtaining public goods. One of them is crowdfunding which means obtaining investment resources from the more or less wide range of participants. This funding tool combines a number of advantages attractive to the public. These include a combination of investment with elements of game and interindividual network cooperation. Apart from the direct goal of attracting investments, the crowdfunding can be used to advertise products or for marketing research. According to our estimations, in the future the crowdfunding may capture at least 5% of the Russian market of retail lending as well as lending to small and medium-sized businesses.